Beyond the couch: A Comparative Lens of Therapist Fatigue in Addiction vs. Non-Addiction Settings Across Delhi NCR - Aishna Chaudhry; Simran Bagga; Dr. Aanchal Chaudhary (The Bioscan, 2025)
Therapists frequently experience emotional burnout and psychological distress due to prolonged exposure to client suffering. In India, where mental health care is under-resourced and highly stigmatized, therapists’ emotional well-being remains underexplored, particularly across different clinical contexts. Treating clients with substance use disorders is often viewed as especially demanding given relapse patterns and resistance, yet therapists in non-addiction clinical settings also navigate complex and taxing issues. The present study examined differences in compassion fatigue, burnout, and compassion satisfaction among therapists working in addiction specialty settings compared to those in non-addiction clinical settings in Delhi NCR. Using purposive sampling, 50 therapists (25 from addiction settings and 25 from non-addiction settings) completed the Professional Quality of Life Scale (ProQOL-5; Stamm, 2010) along with a demographic survey. Independent-samples t-tests were conducted to assess group differences, and correlational analyses explored relationships among the three constructs. It was hypothesized that addiction therapists would report higher compassion fatigue and burnout, and lower compassion satisfaction than non-addiction therapists. Findings highlight the pervasive psychological costs of therapeutic work across clinical settings and underscore the need for context-sensitive emotional support, supervision, and wellness interventions for mental health professionals in India. KEYWORDS: Therapist fatigue, burnout, compassion fatigue, compassion satisfaction, addiction, India